2012
DOI: 10.4028/www.scientific.net/amr.562-564.318
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Behavior of 9SiCr Steel under Different Treatment with Plant Abrasive

Abstract: In this study, the wear behavior of 9SiCr steel under different treatment with plant abrasive was evaluated by using an abrasive rubber wheel tester. The samples’ microstructures were analyzed by a metallurgical microscope, the samples’ worn surface morphology was observed by using SEM.The results show that: With the increasing of hardness of sample, Its wear resistance is greatly improved. Hardness of laser quenching sample is the highest, wear resistance of it is the best, the second is sub temperature sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Several scholars have investigated the wear mechanism of flat die in feed granulators. For example, Zhang et al [5] and Huang et al [6] investigated the wear mechanism of ring die in the granulator and reported that plastic deformation and micrographic cutting mainly occur on the surface of ring die. Wu et al [2] and Jiang et al [4] investigated the extrusion forming mechanism of a ring die granulator.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have investigated the wear mechanism of flat die in feed granulators. For example, Zhang et al [5] and Huang et al [6] investigated the wear mechanism of ring die in the granulator and reported that plastic deformation and micrographic cutting mainly occur on the surface of ring die. Wu et al [2] and Jiang et al [4] investigated the extrusion forming mechanism of a ring die granulator.…”
Section: Introductionmentioning
confidence: 99%
“…Rabinowicz E [3] thought that hardness was a statistical value, soft abrasives mixed with hard particles interacted with soft positions in hard materials, which caused wear. Wu Jin-feng, Zhang wei found [4][5][6], the wear of the alfalfa particle material to the metal material is the result of the role of soft abrasive and hard abrasive. Sufficiently high hardness is the primary prerequisite for metallic material effectively resisting abrasive wear, but there is no linear relationship between the hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%